Topos and Topography of Italy in Contemporary German Artist’s Prose - Matkowska, Ewa (2024)
The article deliberates upon the relationship of artistic creativity and the topos and topography of Italy in German literature in the decades around 2000. Italy is continuously one of the most important references in artist’s texts. The writers create characters that enter a dialogue with the multi-layer European cultural space represented by “the Italian narratives”. The paper deals with the traditional dichotomy of the topos: North – South, light – darkness, ancient culture – Christian culture, life – death, sensuality – spirituality, nature – culture and civilization. The specifics of the connection between artistic creativity and the Italy topos are examined on the basis of three examples: Hanns-Josef Ortheil Rom, Villa Massimo (2015), Feridun Zaimoglu Rom intensiv (2007) and Martin Mosebach Die schöne Gewohnheit zu leben – eine italienische Reise (1997). The analysis focuses on the palimpsests of space, time and text. It is characteristic that the figures move in a topically charged area of Italy and examine their aesthetic points of view. The character construction goes back to the model of a Flâneur, wanderer and traveller who – in contrast to previous epochs – is equipped with communication technologies that enable him to create his own trans-medial message.
Keywords: artist’ novel; Künstlerroman; German literature; Italian Journey; Italy; Rome; palimpsest